Місце та особливості органів Національної поліції у системі суб’єктів протидії проступкам у сфері забезпечення безпеки дорожнього руху в Україні - Солонецький, І. І.; Solonetskyi , I. I. (Європейські перспективи. - 2017. - № 1. - С. 222-227, 2017)
Встановлено та проаналізовано місце Національної поліції України в системі суб’єктів забезпечення безпеки дорожнього руху спеціальної компетенції, з’ясовано особливості її правового статусу. Досліджено основні види адміністративної діяльності Національної поліції України у даній сфері. Визначено та проаналізовано основні завдання та повноваження патрульної поліції України як основного суб’єкта протидії проступкам у сфері забезпечення безпеки дорожнього руху. На підставі аналізу норм чинного законодавства України досліджено компетенцію органів Національної поліції України у сфері забезпечення безпеки дорожнього руху в Україні.

The scientific article is devoted to research of the place and features of the National Police in the general system of subjects of counteraction to offenses in the field of road traffic safety in Ukraine. The specific features of functions and powers of the National Police in this field of activity are considered. The contemporary scientific approaches to classification of subjects of counteraction to offenses in the field of road traffic safety in Ukraine are considered. According to the criteria of authority, structure and legal properties, all subjects of counteraction to offenses in the field of road safety in Ukraine are divided into state and non-state. The system of counteraction to road safety offenses consists of executive state bodies of different levels, among which two groups of subjects were singled out: executive state bodies, whose powers extend to road safety, and executive state bodies of special powers, whose activities are directly aimed at ensuring road traffic safety. Analyzes of the place and specific features administrative and legal status of the National Police in the system of subjects of road safety of special competence was prepared. The main types of administrative activity of the National Police of Ukraine in the field of road traffic safety are studied. The objectives and functions of Patrol service of the National police as a main subject of counteraction to offenses in the field of road traffic safety in Ukraine are analyzed. Through the analysis of normative-legal acts that regulate road safety in Ukraine, the competency of the bodies of the National Police in the field of road traffic safety in Ukraine was prepared.

В статье исследуются место и значение органов Национальной полиции Украины в общей системе субъектов противодействия проступкам в сфере обеспечения безопасности дорожного движения в Украине. На основе анализа современной научной литературы определены критерии классификации субъектов обеспечения безопасности дорожного движения, выделены и охарактеризованы основные группы субъектов в данной сфере. Установлено место Национальной полиции Украины в системе обеспечения безопасности дорожного движения, определены основные задачи и полномочия патрульной полиции как основного субъекта противодействия проступкам в сфере обеспечения безопасности дорожного движения в Украине.
The place and features of the National Police in the system of subjects of counteraction to offenses in the field of road traffic safety in Ukraine
Keywords: дорожній рух; безпека дорожнього руху; суб’єкти забезпечення безпеки дорожнього руху; Національна поліція України; патрульна поліція України; road traffic; road safety; subjects of road safety; National Police of Ukraine; patrol police of Ukraine; дорожное движение; безопасность дорожного движения; субъекты обеспечения безопасности дорожного движения; Национальная полиция Украины; патрульная полиция Украины